PTU-080 Should we all be looking for Marginal Gains in Endoscopy Efficiency?. (June 2019) - Bryce, Kathleen; Tai, Cheh Kuan; Murray, Sam; Fearn, Robert
Abstract : Introduction: Demand for endoscopy in the UK has doubled in the last 5 years. In 2017, 64% of units failed to meet suspected cancer targets despite 66% of units having weekend lists and 27% outsourcing to external providers 1 . UCL Cancer Collaborative (UCLCC) data showed demand can be met by improving efficiency. This is important in a resource-limited setting. Our Quality Improvement (QI) Project aimed to improve efficiency by improving turnaround time, non-attendance and on-the-day cancellations. Methods: The Endoscopy QI fellow, endoscopy unit manager and Gastroenterology service manager participated in the UCLCC Improvement Programme, and utilised QI methodology. We collected data from electronic patient records and scheduling system. At baseline, we identified that underutilisation of lists was multifactorial. We introduced a turnaround nurse role to consent patients. Healthcare assistants (HCAS) and nurses were trained in cannulation. As poor bowel preparation contributed to cancellations, we introduced telephone pre-assessment to educate patients. Finally, the administrative team sent text reminders before appointments. Results: At baseline, our unit performed an average of 7.9 points per list, out of a planned 10. On average, 28.5 patients per month had procedures cancelled on the day due to poor bowel prep or inadequate fasting. After the introduction of pre-assessment, it improved to 23.5 per month, saving 5 procedures which would have had to be rearranged. The average points performed improved to 9.3 points per list. The average DNA rate has improved from 9% to 7% after the introduction of text reminders. After the introduction of the turnaround nurse and HCA cannulation, turnaround time reduced from an average of 18 to 9 minutes between procedures. This could save 90 minutes over a 12-point list. Despite these improvements, only 41.6% of lists are booked for 1–2 points. Inadequate staffing numbers and late start times are contributing factors. A start time audit showed that only 5 out of 27 lists in a week started within 10 minutes of supposed start times, a target for further cycles of this QI project. Conclusions: Multiple small improvements in efficiency can achieve significant impact on productivity. Interventions focused on turnaround time can reduce underuse of list time. Patient-centred approaches to procedural preparation may reduce squandered appointments. Sustainability of these improvements is difficult to assess in the short term but will be promoted by the continuing QI fellow role and implementation of endoscopy QI champions from the administrative and nursing team. Reference: Shenbagaraj, L., Thomas-Gibson, S., Stebbing, J., Broughton, R., Dron, M., Johnston, D. et al. ( 2018) Endoscopy in 2017: A national survey of practice in the UK, Frontline Gastroenterology, pp. 100970. DOI: 10.1136/flgastro-201–00970.